Desiccated vector mosquitoes used for the surveillance of Japanese encephalitis virus activity in endemic southern India - Tewari, S.C; Thenmozhi, V; Arunachalam, N; Philip Samuel, P; Tyagi, B.K (Tropical medicine & international health, 2008)
To monitor Japanese encephalitis virus (JEV) activity in endemic areas of Tamil Nadu, southern India, desiccated vector mosquitoes were screened for JEV antigen using ELISA, from 1996. A total of 133 233 specimens from eight index villages comprising 2816 pools (mainly Culex vishnui subgroup) were tested. Of these, 59 pools (2.1%) were positive for JEV antigen. Control measures were undertaken in positive villages accordingly. The average annual minimum infection rate was 0.8 at the beginning of the study and remained lower for nearly 8 years. A declining trend in JE cases was recorded.